Ideologia e educação : a proposta pedagógica do MST e as escolas do campo de Querência do Norte-PR - Oliveira, Alaíde Paulino Machado de (2006)
The condition of the Brazilian substandard social class points to education as one of the means for liberating country people from the oppression exerted by reactionary men, once, it is assumed that social justice can be implanted by means of formal education, as well as, with the occurrence of the Agrarian Reform. Bearing in mind the conception that "education is as important as the movement Pro-Iand and Pro Agrarian Reform", 'MST', the Brazilian Landless Rural Workers' Movement, has structured an educational proposal whose aim is to work with a different type of school. Such a new school is based on the reality of Brazilian country people. Therefore, it is based on principles such as, education in the country surroundings and involving things related to the country, with the purpose of building up the identity of Landless people. Since its foundation, MST has been investing in education, and through it has been searching for a way to make the individuals better conscious, consequently, aiming at building up a better society. Human formation has been one of its main purposes. It is in this sort of school, seen as an educative environment, that such a human formation is searched for. Therefore, it is in schools, settled down inside MST campings and also, in schools settled down in places where people have already received their lands, that one attempts to work based on the Movement Pedagogy, so that their members can learn under the light of those values in order to build up their identity as Landless People. The target is to make them go ahead with the movement Pro-land and Pro Agrarian Reform. Thus, the aim of the present study is to show the proposal of MST education entailed to the ideological formation of the Movement.